The Melkites in Fatimid Egypt and Syria (1021–1171) - Pahlitzsch, Johannes (Medieval encounters, 2015)
This paper examines the history of the Chalcedonian Melkites in the Fatimid state in the period after the reign of the caliph al-Ḥākim, i.e., from 1021 until the end of the Fatimid caliphate in 1171. For the eleventh century the focus will be on Palestine (before its conquest by the Crusaders). Although the evidence is very fragmentary, the attempt will be made to provide some insights on the development of the situation of the Melkite community under Fatimid rule, its ecclesiastical institutions, its connection with Byzantium, and its intellectual life.